Relationship between perceived stress and resilience with happiness - Pour, Manoochehr Taghi; Ismail, Asmah; Yusop, Yusni Mohamad; Rajabi, Gholamreza (Universidad Tecnica de Manabi, 2022)
This study is to determine the relationship between perceived stress and resilience with happiness. This study used a descriptive, cross-sectional design. A representative sample of 310 pre-university students were selected through multistage sampling. The study utilized Perceived Stress Scale, Resilience Scale, and Subjective Happiness Scale. The finding reveals that there is a difference between males and females' pre-university students in terms of happiness variable. Female subjects are happier compared to males. There are simple and multiple relationships between perceived stress and resilience with happiness among pre-university students. Increased level of resilience and decreased level of perceived stress are associated with students’ happiness. Based on the results, enhancing the students' level of happiness should receive more attention in order to produce professional graduates who are academically competent, and able to adapt to their environment. Directions for future research are discussed.